2008
DOI: 10.1038/cmi.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Murine Dendritic Cells Induced by Incubation with Tumor Cells

Abstract: In vivo studies showed that dendritic cell (DC) dysfunction occurred in tumor microenvironment. As tumors were composed of many kinds of cells, the direct effects of tumor cells on immature DCs (imDCs) are needed for further studies in vitro. In the present study, bone marrow-derived imDCs were incubated with lymphoma, hepatoma and menaloma cells in vitro and surface molecules in imDCs were determined by flow cytometry. Then, imDCs incubated with tumor cells or control imDCs were further pulsed with tumor lysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although literature show a potential role for Tregs in the control of autoimmune or inflammatory diseases (32), the nature of APCs involved in Treg expansion remains poorly understood. Our previous report documented that the tumor cell-DC co-incubation decreased CD80, and CD86 expressions of DCs (9). DCs, especially deficient in CD80 and CD86, appeared to be more efficient than other APCs in inducing TGF-β expansion (33,34).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although literature show a potential role for Tregs in the control of autoimmune or inflammatory diseases (32), the nature of APCs involved in Treg expansion remains poorly understood. Our previous report documented that the tumor cell-DC co-incubation decreased CD80, and CD86 expressions of DCs (9). DCs, especially deficient in CD80 and CD86, appeared to be more efficient than other APCs in inducing TGF-β expansion (33,34).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to tumor cells, tumor microenvironment is comprised of immune cells, fibroblasts, stromal cells and extracellular matrix (1). Previous studies showed that co-incubation of DCs with different tumor cells could down-regulate the abilities of DCs mediating tumor antigenic-specific CTL priming (9) or inducing human Treg expansion (6). Suppressed DCs functions have been reported in various tumor microenvironment models, in tumor-bearing animals, as well as in cancer patients (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow-derived immature dendritic cells (imDCs) were prepared as previously described [ 39 ]. Briefly, bone marrow mononuclear cells were prepared from bone marrow suspensions of C57BL/6 mice by depletion of red cells and then were cultured at a density of 1×10 6 cells/ml in RPMI 1640 complete medium with 10 ng/ml of GM-CSF and 1 ng/ml of IL-4.…”
Section: Methodsmentioning
confidence: 99%
“…Broadly, myeloid cells (MCs) play key roles in mediating tumor suppression through early detection of tumor antigens, initializing recruitment of adaptive immune cells to the tumor microenvironment (TME) and elimination of pre-malignant and early-stage tumor cells (5,6). As such, tumor-induced deregulation of the myeloid compartment can significantly influence tumor progression by stimulating tumorigenesis and enforcing an immunosuppressive microenvironment that undermines the efficacy of immunotherapies (7)(8)(9)(10). Pro-tumorigenic MCs, such as myeloid-derived suppressor cells (MDSCs), regulatory dendritic cells (DC reg ), tumor-associated macrophages and neutrophils (TAMs and TANs, respectively), represent an unique challenge for cancer immunotherapies.…”
Section: Introductionmentioning
confidence: 99%